GAMBARAN AKSEPTOR KB DI KECAMATAN TANIMBAR SELATAN MALUKU - Wahyunita, Vina Dwi; Sari, Marlynda Happy Nurmalita; Setiawati, Irma Fitri; Nuryanti, Erni (Journal of Midwifery Science: Basic and Applied Research, 2023)
One of the problems in Indonesia is the rate of population growth which can cause a population explosion. To overcome this problem, the government implemented a Family Planning (KB) program using contraception. The aim of this research is to find out the picture of acceptors in South Tanimbar District in 2023. This research is a quantitative analytical research with a cross sectional research design. The sampling time was carried out in January-April 2023. Samples were taken using a total sampling of 460 people. Data analysis uses univariate analysis with frequency distribution. The results of the research show that in South Tanimbar District, Maluku, the subdistrict with the highest number of active family planning participants is the subdistrict with the highest number of family planning acceptors being Saumlaki and Olilit Raya, namely 99 people, while the highest number of contraceptive users is injectable family planning at 59.35% followed by implant birth control at 27.61 %.